Why punish? How much?: a reader on punishment - Tonry, Michael H. (Oxford University Press, 2011)
Normative, political, social, psychological, and legal ideas concerning punishment have changed drastically over time, and especially in recent decades. Why Punish? How Much? collects essays from classical philosophers and contemporary theorists to examine these shifts. Gathering a comprehensive set of readings ranging from Kant, Hegel, and Bentham to recent writings on developments in the behavioral and medical sciences, this reader provides a fresh and comprehensive approach to thinking about punishment and sentencing for a broad range of law, sociology, philosophy, and criminology courses.